A narrative review of sociodemographic risk and disparities in screening, diagnosis, treatment, and outcomes of the most common extrathoracic malignancies in the United States - Singh, Sarah (J Thorac Dis, 2021)
There is a well-established association between multiple sociodemographic risk factors and disparities in cancer care. These risk factors include minority race and ethnicity, low socioeconomic status (SES) including low income and education level, non-English primary language, immigrant status, and residential segregation, and distance to facilities that deliver cancer care. As cancer care advances, existing disparities in screening, treatment, and outcomes have become more evident. Lung cancer remains the most common and fatal malignancy in the United States, with breast, colorectal, and prostate cancer being the three most common and deadly extrathoracic malignancies. Achieving the best outcomes for patients with these malignancies relies on strong physician-patient relationships leading to robust screening, early diagnosis, and early referral to facilities that can deliver multidisciplinary care and multimodal therapy. It is likely that challenges experienced in developing patient trust and understanding, providing access to screening, and building referral pipelines for definitive therapy in lung cancer care to vulnerable populations are paralleled by those in extrathoracic malignancies. Likewise, progress made in delivering optimal care to all patients across sociodemographic and geographic barriers can serve as a roadmap. Therefore, we provide a narrative review of current disparities in screening, treatment, and outcomes for patients with breast, prostate, and colorectal malignancies.